2014
DOI: 10.1194/jlr.m048504
|View full text |Cite
|
Sign up to set email alerts
|

Methylation at CPT1A locus is associated with lipoprotein subfraction profiles

Abstract: This article is available online at http://www.jlr.orgCholesterol concentrations from lipoprotein fractions are some of the most commonly used clinical biomarkers of cardiovascular and metabolic disease risk ( 1 ). However, LDL cholesterol and HDL cholesterol concentrations do not account for all lipid-based CVD risk ( 1 ). In addition, the causal role of HDL cholesterol with CVD is debated ( 2 ). Thus, alternative lipid biomarkers of CVD are useful for gaining a more complete CVD risk profi le and for explori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 32 publications
7
56
0
Order By: Relevance
“…Methylation at the top CPT1A locus explained 12% of TG variation in the discovery cohort (Genetics of Lipid Lowering Drugs and Diet Network (GOLDN), CD4+ lymphocytes, n=991) and 6% in the replication cohort (Framingham Heart Study, whole blood, n=1261) [12]. Subsequent studies have replicated the observed association with lipids [7, 15, 16] and lipoprotein subfraction profiles [17], as well as linked CPT1A methylation with obesity traits [18, 19], metabolic syndrome [20], and hypertriglyceridemic waist [21] in diverse populations. Interestingly, CPT1A loci were also shown to be differentially methylated in Dutch Hunger Winter survivors exposed to famine in utero , associating with both birth weight and serum LDL cholesterol levels later in life [22] and providing a possible mechanism for the well-known adverse metabolic sequelae of prenatal malnutrition.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Methylation at the top CPT1A locus explained 12% of TG variation in the discovery cohort (Genetics of Lipid Lowering Drugs and Diet Network (GOLDN), CD4+ lymphocytes, n=991) and 6% in the replication cohort (Framingham Heart Study, whole blood, n=1261) [12]. Subsequent studies have replicated the observed association with lipids [7, 15, 16] and lipoprotein subfraction profiles [17], as well as linked CPT1A methylation with obesity traits [18, 19], metabolic syndrome [20], and hypertriglyceridemic waist [21] in diverse populations. Interestingly, CPT1A loci were also shown to be differentially methylated in Dutch Hunger Winter survivors exposed to famine in utero , associating with both birth weight and serum LDL cholesterol levels later in life [22] and providing a possible mechanism for the well-known adverse metabolic sequelae of prenatal malnutrition.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In humans, CPT1A deficiency causes hepatomegaly, hepatic steatosis, and metabolic perturbations (Bennett and Santani, 1993), while in rats, Cpt1a expression was shown to be down-regulated during steatosis in male rats consuming a high-fat diet (Xie et al , 2010), while a moderate overexpression of Cpt1a in obese male rats increased hepatic fatty acid β-oxidation and decreased hepatic triglyceride accumulation (Stefanovic-Racic et al , 2008). Cpt1a expression has been shown to be regulated by the binding of transcription factors (including C/EBPβ and SREBP1 (Attia et al , 2011; Thakran et al , 2013) in cell culture, as well as with altered DNA methylation in humans (Frazier-Wood et al , 2014; Irvin et al , 2014). However, despite the critical regulatory role of this gene in hepatic energy metabolism and lipid accumulation, and the proposed role of BPA exposure in NAFLD development, no studies have specifically assessed the gene’s potential epigenetic regulation in response to developmental BPA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of the Journal , Frazier-Wood et al ( 8 ) reported the novel fi ndings of signifi cant negative correlations between methylation levels at two CpG sites in the CPT1A locus and plasma levels of VLDL and LDL. Methylation levels were assessed in CD4+ T-cells isolated from peripheral blood DNA using the HM450K array.…”
mentioning
confidence: 99%